Bone Marrow-Derived Clonal Mesenchymal Stem Cells as a Source of Cell Therapy for Promoting Vocal Fold Wound Healing. (February 2013) - Kim, Young-Mo; Yi, TacGhee; Choi, Jeong-Seok; Lee, Songyi; Jang, Yun Ho; Kim, Chul-Ho; Song, Sun U.; Lim, Jae-Yol
Objectives: We investigated whether mouse bone marrow-derived clonal mesenchymal stem cells (BM-cMSCs) could promote vocal fold (VF) wound healing by using a xenograft animal model. Methods: Homogeneous BM-cMSCs isolated by a subfractionation culturing method from the bone marrow aspirates of green fluorescent protein transgenic mice were injected into the VFs of rabbits immediately after direct mechanical injury. Macroscopic, biomechanical (rheometric), histologic, immunohistochemical, and transcriptional evaluations were performed on the scarred VFs 1 to 3 months after injury. Engraftment of the implanted BM-cMSCs was determined by detection of green fluorescent protein cells in the recipient VF by confocal microscopy. Results: The BM-cMSC-treated VFs showed improved morphological properties and viscoelasticity as compared to control VFs injected with phosphate-buffered saline solution. Histologic and immunohistochemical evaluations showed less excessive collagen deposition and increased density of glycosaminoglycans in the BM-cMSC-treated VFs as compared to the control VFs at 3 months after injury (p = 0.003 and p = 0.037, respectively). BM-cMSC transplantation led to a significant attenuation of fibronectin (p = 0.036) and transforming growth factor β1 (p = 0.042) messenger RNA expression at 1 month after injury. Green fluorescent protein-expressing BM-cMSCs engrafted in recipient VFs were found at 1 month after implantation. Conclusions: BM-cMSCs appeared to survive in the injured xenogeneic VFs after transplantation for up to 1 month and favorably enhanced the wound healing of VFs after injury. We conclude that BM-cMSCs are a possible source of cell therapy for vocal fold regeneration.